The effect of fine particulate matter exposure on allergic rhinitis of adolescents aged 10–13 years: A cross-sectional study from Chongqing, China - Qiu, Chunlan; Feng, Wei; An, Xizhou; Liu, Fangchao; Liang, Fengchao; Tang, Xian; Zhang, Ping; Liang, Xiaohua (Frontiers in Public Health, 2022)
Background: Allergic rhinitis (AR) has become a tremendous disease burden worldwide. Only a few studies were exploring the effects of environmental exposure on the prevalence of AR in children in China. Methods: In the present study, we investigated the associations of environmental exposure (including fine particulate matters less than 2.5μm (PM2.5), air humidity, temperature, and passive smoking) with AR in adolescents aged 10-13 years in Chongqing. Data from 4146 participants in urban and rural areas between March 2019 and May 2019 were collected. Results: The overall prevalence of AR was 17.50% in adolescents. After adjusting for other covariates, AR was positively associated with the annual mean PM2.5 concentration, monthly mean PM2.5 concentration, air temperature, and negatively related to air humidity. Further, annual mean PM2.5 was positively associated with the risk of AR after even adjusting for air temperature and humidity. Passive smoking (PS) was marginally associated with a high risk of AR. Conclusion: High PM2.5 exposure, high air temperature, and low air humidity were associated with a high risk of AR in adolescents. Our findings have potential implications for public health strategies and interventions aimed at reducing the burden of AR in adolescents.